2020
DOI: 10.3390/jcm9020351
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker-Based Preoperative Risk Stratification for Patients Undergoing Non-Cardiac Surgery

Abstract: Perioperative morbidity and mortality remains a substantial problem and is strongly associated with patients’ cardiac comorbidities. Guidelines for the cardiovascular assessment and management of patients at risk of cardiac issues while undergoing non-cardiac surgery are traditionally based on the exclusion of active or unstable cardiac conditions, determination of the risk of surgery, the functional capacity of the patient, and the presence of cardiac risk factors. In the last two decades, strong evidence sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
(46 reference statements)
0
1
0
9
Order By: Relevance
“…В других странах придерживаются другого подхода, например, предложен так называемый «Швейцарский алгоритм» [12]. Оценка уровня BNP или NT-proBNP проводилась у пациентов с низким функциональным статусом, при нормальных значениях они могут быть подвергнуты хирургическому вмешательству без дальнейшего тестирования.…”
Section: биомаркерыunclassified
See 1 more Smart Citation
“…В других странах придерживаются другого подхода, например, предложен так называемый «Швейцарский алгоритм» [12]. Оценка уровня BNP или NT-proBNP проводилась у пациентов с низким функциональным статусом, при нормальных значениях они могут быть подвергнуты хирургическому вмешательству без дальнейшего тестирования.…”
Section: биомаркерыunclassified
“…Последние годы характеризуются появлением новых рекомендаций в смежных областях (диагностика и лечение хронического коронарного синдрома [7], четвертое универсальное определение инфаркта миокарда [8]), а также публикацией большого числа работ по оценке риска некардиальных операций. Эксперты пришли к различным алгоритмам оценки и коррекции кардиального риска [9][10][11], несмотря на одинаковый исходный набор результатов исследований, что отражено в недавних обзорах [12,13]. Следствием этого стали публикации по валидизации новых алгоритмов и их сопоставлению с существовавшими ранее рекомендациями.…”
unclassified
“…Pacientes con niveles normales puede someterse a cirugía sin más pruebas, mientras que los pacientes con elevación de BNP o NT-proBNP son de alto riesgo, deben someterse a un tratamiento cardiológico y la vigilancia de troponinas es recomendado diariamente durante 48 a 72 h. Un cambio de ≥ 20% se interpreta como significativo y se debe diferenciar si la injuria miocárdica es por causa isquémica o no isquémica. Si la causa es isquémica, se procede a la clasificación de infarto tipo I (ruptura de placa) o tipo II (desbalance entre oferta y demanda) [6]. Las guías de la CSC recomiendan obtener diariamente medidas de troponina durante 48-72 h después de la cirugía no cardíaca en pacientes con un riesgo inicial > 5% de muerte cardiovascular o IAM no mortal 30 días después de la cirugía, es decir, pacientes con una medición elevada de NT-proBNP/BNP antes de la cirugía o, si no hay medición de NT-proBNP / BNP antes de la cirugía, en aquellos que tienen una puntuación RCRI ≥ 1, de 45-64 años con enfermedad cardiovascular significativa o de 65 años o más [4].…”
Section: -Biomarcadoresunclassified
“…Sin embargo, a pesar de la eficacia demostrada de estos biomarcadores, no es posible realizarlos de forma rutinaria a todos los pacientes, actualmente, no hay un biomarcador que sea 100% específico y 100% sensible, y se pueden elevar en condiciones de ausencia real de isquemia miocárdica, por lo que tratar a pacientes por una condición no existente podría ser dañino [6], [7].…”
Section: -Biomarcadoresunclassified
“…With the development of high-sensitivity troponin (Hs-TnI) for early diagnosis of perioperative acute myocardial infarction, etiological identification of perioperative myocardial injury and other related research[ 10 ], more biomarkers have been identified for use in cardiac risk assessment[ 11 , 12 ], but there is no widely recognized quantitative monitoring index of perioperative cardiac function[ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%